Role of Eco-adventure Tourism on Sustainable Rural Community Development in Nepal - Tiwari, Surendra; Thapa, Ajay; Timilsina, Jagat (International Journal of Social Sciences and Management, 2025)
Eco-adventure tourism is an emerging form of tourism in Himalayan countries worldwide. Nepal being a Himalayan country is growing as a destination for eco-adventure tourism. This paper examines the role of eco-adventure tourism on sustainable community development in rural settlements along the Annapurna Sanctuary Trail (AST), Nepal through the perspectives of local inhabitants with 120 on-site surveys, five key informant interviews, six focus group discussions, in-person observations, and archival studies. The study revealed significant benefits of eco-adventure tourism on income generation, infrastructure development, cultural preservation, community empowerment, social cohesion, and environmental conservation in rural communities in Nepal. Furthermore, the study disclosed that eco-adventure tourism has resulted in sustainable community development by generating livelihood assets: natural capital, financial capital, socio-cultural capital, human capital, and physical capital, along with AST. This paper suggested key policy initiatives particularly environmental protection, effective waste disposal and management, increased engagement of marginalised and economically disadvantaged groups in eco-adventure tourism activities, cultural heritage preservation, and the integration of traditional agricultural and occupational practices into tourism development strategies to strengthen sustainable community development in Nepal. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 60-71